Laporan Kasus : Skreening Demensia Pada Seorang Lansia Laki- Laki Dengan Aktifitas Dharma Gita Sebagai Faktor Protektif Demensia Yang Berbasis Budaya Bali - Rahayu, Ni Wayan Saka; Wulan, Ni Made Citra Riesti; Putra , Putu Risdianto Eka (Jurnal Global Ilmiah, 2025)
Dharma Gita is a vocal art that is included in the traditions and culture of the Balinese people. Cultural preservation efforts are closely related to the role of the elderly, as heirs of ancestral values that will later be passed on to the younger generation. As the elderly population in Indonesia increases, it is expected that there will be an increase in health problems in this age group, one of which is dementia. Dementia is a syndrome of significant decline in intellectual ability and memory, to the point of interfering with social and professional activities. In Indonesia, the number of people with dementia is estimated to reach 1.2 million in 2016 and could jump to 2 million by 2030 and 4 million by 2050. This case report aims to find out the results of Dementia screening in an elderly man with Dharma Gita activities as one of the potential non-pharmacological therapies. Methods: Interview and filling out the MMSE questionnaire. Case illustration: A man with the initials IKM (73 years old) has complaints of confusion, decreased concentration, forgetting steps in doing something that has been felt since 6 months, BPH history, MMSE score of 29 which shows normal. According to patients who participated in Dharma Gita activities, this is one of the positive activities. When doing this activity, the patient feels a quiet, peaceful and calm mind. When reading the lyrics of one of the Dharma Gita, issuing voice after voice until it becomes a verse of one song is quite a thing to sharpen vision and memory, in fact, it is not uncommon for patients to feel carried away into the meaning of the Dharma Gita. Discussion: In the context of dementia, the Dharma Gita functions as a vocal therapy medium that is able to express a variety of emotions, such as anger, sadness, happiness, fear, and inner pressure. Through the chanting of the Dharma Gita, individuals are invited to achieve good values in accordance with religious teachings and traditions in Bali. If chanted correctly and correctly, the Dharma Gita is believed to be able to help control the mind (manah) in a positive way. Conclusion: The participation of SMEs (73 years old) in cultural-social activities such as Dharma Gita is suspected to have a protective role for the cognitive function of the elderly as well as a form of cultural preservation. More sensitive neuropsychological screening, neuroimaging examinations for diagnosis enforcement, and prospective studies are needed to systematically evaluate the influence of the Dharma Gita on MMSE scores and dementia incidence.